Rationale for a Multimodality Strategy to Enhance the Efficacy of Dendritic Cell-Based Cancer Immunotherapy - Datta, Jashodeep; Berk, Erik; Cintolo, Jessica A.; Xu, Shuwen; Roses, Robert E.; Czerniecki, Brian J. (Frontiers in Immunology, 2015)
Dendritic cells (DC), master antigen-presenting cells that orchestrate interactions between the adaptive and innate immune arms, are increasingly utilized in cancer immunotherapy. Despite remarkable progress in our understanding of DC immunobiology, as well as several encouraging clinical applications — such as DC-based sipuleucel-T for metastatic castration-resistant prostate cancer — clinically effective DC-based immunotherapy as monotherapy for a majority of tumors remains a distant goal. The complex interplay between diverse molecular and immune processes that govern resistance to DC-based vaccination compels a multimodality approach, encompassing a growing arsenal of antitumor agents which target these distinct processes and synergistically enhance DC function. These include antibody-based targeted molecular therapies, immune checkpoint inhibitors, therapies that inhibit immunosuppressive cellular elements, conventional cytotoxic modalities, and immune potentiating adjuvants. It is likely that in the emerging era of “precision” cancer therapeutics, tangible clinical benefits will only be realized with a multifaceted—and personalized—approach combining DC-based vaccination with adjunctive strategies.